Analisis Faktor-Faktor yang Mempengaruhi Minat Pemanfaatan Teknik Audit Sekitar Komputer - Dian Saputra, I Wayan; Dwirandra, A.A.N.B. (E-Jurnal Akuntansi, 2015)
Interests utilize audit techniques around the computer is still low when this technique is simple but the most important applied when auditing company computer-based accounting process. This study aims to determine the factors that affect the interests of the utilization of audit techniques around the computer by using the model of acceptance of the Unified Theory of Acceptance and Use of Technology ( UTAUT ). This study hypothesizes performance expectations , expectations of the business, and social factors as independent variables and the dependent variable of interest as the utilization. Data collected by distributing questionnaires to the auditor in public accounting firms that are members of the Indonesian Institute of Certified Public Accountants ( IAPI ) Bali region as respondents using purposive sampling method of sampling. The analysis technique used is multiple linear regression. These results indicate that the variable performance expectations, expectations of the business, and social factors partially significant positive effect on the interest in the use of audit techniques around the computer.
Keywords: UTAUT Model, Performance Expectations, Business Expectations, Social Factors, Interests Utilization